Effect of Sugar Addition on the Electric Current Strength of Mixtures with Vinegar, Lime Extract, Coffee, Salt Solution, and 70% Alcohol - Wardana, Dian; Ramadhan, Dwi Sapri; Fahmi, Jam'an; Safitri, Wulan Dwi; Siregar, Ida Cathy Everyanti; Silalahi, Sarina Septiani; Zubir, Moondra; Siregar, Nurdin (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
This study aims to examine the electric current strength of sugar mixed with various electrolyte and non-electrolyte solutions. The research employed an experimental approach using vinegar, lime extract, coffee solution, salt solution, and 70% alcohol combined with sugar solutions. A battery system and a digital multimeter were utilized to measure the resulting current in each mixture. The findings indicate that increasing the amount of sugar leads to a reduction in current strength, whereas decreasing the sugar content results in a higher current output.